Many-Facet Rasch Model (MFRM) for Digital Citizenship Measurement Analysis in Islamic Schools: A Bibliometric Review - Vita Fitriatul Ulya; Fikiy Afriyanto; Suparto; Kusaeri; Vacharee Dedduang (MUMTAZ : Jurnal Pendidikan Agama Islam, 2025)
The increasing need for Digital Citizenship competencies in education requires the availability of assessment instruments that are objective, valid, and in line with the challenges of digital ethics in the modern era. This study aims to map the global development of the use of the Many-Facet Rasch Model (MFRM) in the analysis of Digital Citizenship (DC) instruments and identify the implications of its application for the development of assessments in Islamic schools. Using the Scopus and ERIC data-based bibliometric analysis design, this study processed 143 publications through the bibliometrix device at R-Studio, including publication trend analysis, scientific collaboration, thematic structure, and citation network. The results of the study show that the integration of MFRM in digital citizenship assessment provides a strong methodological foundation to overcome the issue of rater bias and strengthen the objectivity of performative evaluation, especially in the context of Islamic Schools which require digital character assessments based on moral values, morals, and ethical responsibility in accordance with Islamic education principles. This study concludes that MFRM is a strategic approach to improve the quality of DC assessments in a fair and value-based manner, as well as open up opportunities for innovation of digital character evaluation instruments in Islamic schools. Further studies are recommended to test the empirical implementation of MFRM-based instruments and Differential Facet Functioning (DFF) analysis in madrasah and cross-cultural contexts.